Analysis of domestic water consumption in Malaysia - Ali Hassan, Filzah (2013)
Knowledge about water consumption is very important for water resources development, management and planning at both short-and long-term scales as well as sustainable development of a country. As water demand depends on various factors, it is very important to identify those factors and to know the influence of those factors in water consumption in order to better manage the water resources. The objective of the present research is to assess the trend of water consumption per capita in different states in Malaysia over the time period of 1991-2010, where it is found that all states have significantly increase their water consumption per capita with highest magnitude of increment +7 litres per capita per year for Negeri Sembilan. Other objective is to measure the influence of various factors on domestic water consumption in different states of Malaysia. As economic and climate variables have significant effects on water consumption, data of domestic water use, water price, per capita GDP and averaged annual rainfall of different states of Malaysia over the time period 1991-2010 are analysed in this project by using various statistical methods such as partial correlation and multiple-regression in order to measure the influence of different factors on domestic water consumption. It is found that the most influential factor on water consumption in Malaysia is GDP. In Johor, water price and rainfall are found to be the influence factors, while in Terengganu water price found to be the significant influential factor. Sensitivity analysis is also carried out to understand how variation of these factors changes water consumptions. Both statistical methods; multi-linear regression and artificial neural network can examine the extend of linear and non-linear relationship between the variables that have impact on water consumption level and predict accurately with reasonable amount of error.